So I am given the sum of the expression in the following link: http://www.wolframalpha.com/input/?i=lim+as+n-%3Einf+(+(cos(n))^2+%2F(n^2+%2B+1)+*+n^2+)
I have a_n = (cos(n))^2 /(n^2 + 1) and b_n = 1/n^2
on the step, lim n=>inf (cos(n))^2 /(n^2 + 1) * n^2, I don't know what to do with (cos(n))^2 since it fluctuates however, what I did is I just assumed it to be a negligible constant other than 0 (such as 1) and my next step is lim n=>inf n^2/(n^2 +1) = 1 and I then concluded that the answer is convergent (which it is) however I really feel that I just "got lucky" and would appreciate it if someone could explain the (cos(n))^2 part.
Any help would be greatly appreciated!
Thanks in advance!